Reset middle east : old friends and new alliances - Kinzer, Stephen ([S.l.] : I. B. Tauris & Company, 2010)
Peace and democracy in the Middle East have been the aim of world leaders for generations, yet the US, UK or their closest allies in the region have been behind nearly every war in the Middle East in the last century. How did the West get everything so wrong? In this concise and readable book Stephen Kinzer takes the reader on a tour of modern Middle Eastern history, highlighting the errors, alliances and betrayals all acted out for what was shortsightedly seen as being in the interest of Western states. His insight and historical knowledge culminate in the startling conclusion that the US has allied with the wrong Middle Eastern states. Rather than Israel and Saudi Arabia, America's natural allies- according to Kinzer's controversial but closely reasoned analysis- should be Iran and Turkey.